Implementation of wahdah method on the mathematics learning - Lutfi, Sunisa; Sunanto, Rahma Faelasofi; Nihayati, Nihayati (Desimal: Jurnal Matematika, 2021)
The problem in this research is the low student learning outcomes that are thought to be due to the use of teaching methods, where teachers still dominate the teaching and learning process. Sampling was done by using the cluster random sampling technique. The research instrument used was a test consisting of 5 items in the form of a description. The data analysis technique used the t-test because the population research data were normally distributed and homogeneous. The difference in the average of mathematics learning outcomes of students between the experimental class and the control class is shown by the results and the average of mathematics learning outcomes of students in the experimental class is 77.93 higher than the average mathematics learning outcomes of students in the control class 55.72 which means that there is the influence of the Wahdah method on mathematics learning outcomes of 22.21.